Improving cloud based encrypted databases - Cominetti, Eduardo Lopes; Simplicio Junior, Marcos Antonio (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2020: Companion Proceedings of the 20th Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2020.19271, 2020)
Databases are a cornerstone for the operation of many services, such as banking, web stores and even health care. The cost of maintaining such a large collection of data on-premise is high, and the cloud can be used to share computational resources and mitigate this problem. Unfortunately, a great amount of data may be private or confidential, thus requiring to be protected from both internal and external agents. Moreover, this data needs to be manipulated to provide useful information to its owner. In this dissertation, we propose modifications to CryptDB, a state-of-the-art encrypted cloud database, aiming to enhance its efficiency, flexibility and security; this is accomplished by improving or changing its underlying cryptographic primitives.